2003
DOI: 10.1002/rmv.402
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases conserved in herpesviruses potentially share a function mimicking the cellular protein kinase cdc2

Abstract: Herpesviruses encode protein kinases. A subset of these proteins, represented by HSV-1 UL13, are conserved throughout all members of the Herpesviridae, and here, are designated CHPKs (conserved herpesvirus protein kinases). In addition to conserved gene products like CHPKs, herpesviruses encode genes specific to respective herpesviruses. When acting upon conserved viral gene products or cellular factors, CHPKs may play conserved roles in the life cycles of herpesviruses. CHPKs may also express unique functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 79 publications
2
66
0
Order By: Relevance
“…Although the kinase is conserved among herpesviruses, CHPK from different herpesvirus subfamilies show considerable variation in amino acid sequence. Although some sequence preferences for substrate specificity have been described for individual CHPK, there is no consensus phosphorylation sequence for all CHPK (10,30,95,96,100). Despite these differences, partial functional conservation has been reported (193).…”
Section: Herpesvirusesmentioning
confidence: 99%
“…Although the kinase is conserved among herpesviruses, CHPK from different herpesvirus subfamilies show considerable variation in amino acid sequence. Although some sequence preferences for substrate specificity have been described for individual CHPK, there is no consensus phosphorylation sequence for all CHPK (10,30,95,96,100). Despite these differences, partial functional conservation has been reported (193).…”
Section: Herpesvirusesmentioning
confidence: 99%
“…Previous work demonstrated that ␣-, ␤-, and ␥-herpesviruses encode viral protein kinases, which are represented by HSV-1 ULl3, VZV ORF47, human cytomegalovirus UL97, human herpesvirus-6 U69, EBV EGLF4, KSHV ORF36, and rhesus rhadinovirus ORF36 (5,42,43). Similar to cellular serine/threonine protein kinases, these viral kinases contain 11 subdomains; a conserved lysine residue in subdomain II was important for kinase activity (44,45).…”
Section: Orf36 Viral Protein Kinase Is Phosphorylated On Serine-mentioning
confidence: 99%
“…VZV ORF47 null mutants show replication deficiency and the inability to phosphorylate several viral proteins (15,49,50). In addition to phosphorylating viral targets, cellular targets including casein kinase II ␤, EF-1␦, p60, and RNA polymerase II serve as substrates for herpesvirus protein kinases (5,42,(51)(52)(53). Demonstrating conserved function between herpesvirus protein kinases, chimeric viruses expressing substituted protein kinases from other herpesviruses are partially able to compensate for lost function (54).…”
Section: Orf36 Viral Protein Kinase Is Phosphorylated On Serine-mentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses commandeer host cell machinery to synthesize viral proteins needed for successful replication. For example, UL13 and UL97, orthologous kinases encoded by herpes simplex type I (HSV1) and human cytomegalovirus (HCMV), respectively, are functionally similar to the cellular kinase CDC2/CDK1 and phosphorylate several cellular functional targets of cyclin-dependent kinases, including elongation factor 1δ (EF1δ) (29) and pRB (30). Herpesviral kinases are also known to phosphorylate several different members of the cellular DNA damage response pathway.…”
Section: Discussionmentioning
confidence: 99%